Learning from experience – Re-design of the course “Biomedicine for veterinary students” - Heidemann Olsen, Rikke (Improving University Science Teaching and Learning, 2023)
The course “Biomedicine” was hold for the first time during the spring 2014 (2x8 weeks). It is a master course for veterinary students and compromising a full degree of biomedicine for veterinary students, equaling 26.5 ECTS. The course is very comprehensive, with not less than four course responsible and 34 different teachers involved. The course had five different themes, e.g. “cancer” and “lifestyle diseases”, and the idea was that the course should be a continuous multidisciplinary learning process. Finally, the exam should allow the students demonstrate an overview of a large area, rather than very detailed knowledge of only a minor area. However, after completion of the course and the exams, it is obvious that a number of areas could be improved, especially between the intended learning outcome and teaching and learning activities. The project is divided into two parts; part 1 is an introduction part, and part 2 analyzing the major pedagogic challenges for learning in the course in the present form, and suggests actions to develop the course to be hold in the spring 2015. The analyses will be based on my own experience as a teacher, planner and censor at the course, student-evaluations and oral interviews with students.